Libras pernambucana: subsidies for a regional lexicographic proposal - Klimsa, Severina Batista de Farias (2022)
This article presents a fragment of a research in progress to create a dictionary entitled “Libras Pernambucana”, by the Research Group and Studies of the Lexicon of Libras – GRUPELL at UFPE, with signs of the Brazilian Sign Language used by the deaf community in Pernambuco. The objective is to compose a significant corpus of Libras, taking into account the regionalism present in the signs found in the micro and macro regions of the State and expressions that are typical of Pernambuco. The work, when finished, will have a printed version and another in digital format. Our intention is for the dictionary to be used to search for signs that are used by deaf people in Pernambuco; as support material for the teaching/learning process of school contents at different levels of Basic Education, in the learning of Libras in Higher Education and in the production of didactic material for the deaf’s education.